Analisis Komparatif Kualitas Produk Kopi Gunung Sanggabuana Loji Karawang - Robby Fauji; Sihabudin; Yudi Firmansyah (LPPM Universitas Buana Perjuangan Karawang, 2023)
A B S T R A C TThe area to the south of Karawang, to be precise in Mekarbuana Village, Tegalwaru District, is a protected area used as a tourist area. The main object is the natural tourism of Mount Sanggabuana with an altitude of 1,074 mdpl.. One of the potentials in Mekarbuana Village is the potential for coffee farming, for available rice fields covering an area of 1.71 km², plantations covering an area of 6.01 km² with forest covering an area of 1.2 km² and ponds or ponds covering an area of 0.02 km². The data analysis method used is quantitative research and uses a quantitative descriptive research method design: a comparative study. The sample used in this study were 98 respondents who were consumers in Karawang Regency who had bought